2017
DOI: 10.1007/s11665-017-3114-8
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Behavior and Reactivity of Molten Silicon with h-BN Substrate at Ultrahigh Temperatures up to 1750 °C

Abstract: For a successful implementation of newly proposed silicon-based latent heat thermal energy storage systems, proper ceramic materials that could withstand a contact heating with molten silicon at temperatures much higher than its melting point need to be developed. In this regard, a non-wetting behavior and low reactivity are the main criteria determining the applicability of ceramic as a potential crucible material for long-term ultrahigh temperature contact with molten silicon. In this work, the wetting of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…In contrast to the pure h-BN sample, weak Si drop vibrations were observed on the composite substrate only for few seconds after the melting of Si. As we have concluded in our previous work, [7] the drop vibration effect originates from the substrate dissolution followed by a releasing of overbalanced nitrogen through gas/ liquid and gas/solid interfaces. Thus, it seems that highly heterogeneous structure of the composite substrate composed of h-BN matrix and at least four phases (primary SiC and ZrO 2 as well as secondary ZrB and ZrB 2 ) somehow suppresses this phenomenon.…”
Section: B Wetting and Spreading Behaviorsupporting
confidence: 62%
See 3 more Smart Citations
“…In contrast to the pure h-BN sample, weak Si drop vibrations were observed on the composite substrate only for few seconds after the melting of Si. As we have concluded in our previous work, [7] the drop vibration effect originates from the substrate dissolution followed by a releasing of overbalanced nitrogen through gas/ liquid and gas/solid interfaces. Thus, it seems that highly heterogeneous structure of the composite substrate composed of h-BN matrix and at least four phases (primary SiC and ZrO 2 as well as secondary ZrB and ZrB 2 ) somehow suppresses this phenomenon.…”
Section: B Wetting and Spreading Behaviorsupporting
confidence: 62%
“…High purity Si and commercial sintered h-BN composite having the nominal phase composition of (h-BN + SiC + ZrO 2 ) were used for the sessile drop wetting test. As in our previous work, [7] the selected Si material was amorphous polysilicon from the commercial Siemens process, with a purity of 7N. [14] The commercially available (h-BN + SiC + ZrO 2 ) hot isostatically pressed composite HeBoSint Ò O120 (Henze, Germany), was used as substrate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported values of the equilibrium contact angle h measured for Si/h-BN couples at T < 1500°C are within the range of 95°-145°(e.g., Ref 4,5). In our previous work (Ref 6), it was found that the non-wetting behavior of the Si/h-BN system is maintained up to 1650°C, while a non-wetting-to-wetting transition takes place at higher temperatures. It has also been evidenced that the involved reactivity mechanism under static argon atmosphere is mostly based on the h-BN dissolution in molten Si (the dissolution rate depends on temperature), followed by a reprecipitation of h-BN platelets during cooling.…”
Section: Introductionmentioning
confidence: 93%